Confocal Microscopy in Biopsy Proven Argyrosis - Melis Palamar; Suzan Guven Yilmaz; Taner Akalin; Sait Egrilmez; Ayse Yagci (Case Reports in Ophthalmological Medicine)
Purpose. To evaluate the confocal microscopy findings of a 46-year-old male with bilateral biopsy proven argyrosis. Materials and Methods. Besides routine ophthalmologic examination, anterior segment photography and confocal microscopy with cornea Rostoch module attached to HRT II (Heidelberg Engineering GmbH, Heidelberg, Germany) were performed. Findings. Squamous metaplastic changes on conjunctival epithelium and intense highly reflective extracellular punctiform deposits in conjunctival substantia propria were detected. Corneal epithelium was normal. Highly reflective punctiform deposits starting from anterior to mid-stroma and increasing through Descemet’s membrane were evident. Corneal endothelium could not be evaluated due to intense stromal deposits. Conclusion. Confocal microscopy not only supports diagnosis in ocular argyrosis, but also demonstrates the intensity of the deposition in these patients.